2017
DOI: 10.1089/ind.2016.0018
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Saccharification and Fermentation of PretreatedEucalyptus grandisUnder High Solids Loading

Abstract: Whole Eucalyptus grandis trees (including bark, branches and leaves) were investigated as a potential feedstock for bioethanol production. To demonstrate and maximize ethanol production, unwashed steam exploded wood chips (SEWC) were used as substrates in high solids load simultaneous saccharification fermentations (SSF) with an industrial Saccharomyces cerevisiae strain (Fali Ò ). Under optimized SSF conditions-20 wt% solids, 60 filter paper units (FPU)/g glucan, and 36°C-ethanol titer and glucan-to-ethanol y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 50 publications
2
7
0
Order By: Relevance
“…The results obtained in this work can be positively compared with the ones reported in literature using SO 2 -catalyzed steam pretreated spruce bark, in which 87% of ethanol yield was obtained by separate hydrolysis and fermentation (SHF) (Frankó et al, 2015). The whole Eucalyptus grandis tree (including barks, branches and leaves) was pretreated by steam explosion and used as substrate for ethanol production, achieving an ethanol yield of 90% using 20% of solids and 60 FPU/g (McIntosh et al, 2017). As far as we know, there are no studies for bioethanol production from E. nitens bark using an organosolv process.…”
Section: Simultaneous Saccharification and Fermentation Of Delignifiesupporting
confidence: 52%
“…The results obtained in this work can be positively compared with the ones reported in literature using SO 2 -catalyzed steam pretreated spruce bark, in which 87% of ethanol yield was obtained by separate hydrolysis and fermentation (SHF) (Frankó et al, 2015). The whole Eucalyptus grandis tree (including barks, branches and leaves) was pretreated by steam explosion and used as substrate for ethanol production, achieving an ethanol yield of 90% using 20% of solids and 60 FPU/g (McIntosh et al, 2017). As far as we know, there are no studies for bioethanol production from E. nitens bark using an organosolv process.…”
Section: Simultaneous Saccharification and Fermentation Of Delignifiesupporting
confidence: 52%
“…1 a–e). McIntosh et al. (2017) also reported that the available glucose was rapidly converted to ethanol by the yeast in the first 6–12 h after inoculation in SSF and that 90% of ethanol production occurred during this period.…”
Section: Resultsmentioning
confidence: 88%
“…Rapid conversion of available glucose to ethanol by yeast in the first 6 to12 h after inoculation in SSF was reported by McIntosh et al (2017) who found that 90% of ethanol production occurred during this period. As fed-batch substrate feeding strategy was adopted in the present study, continuous ethanol production was monitored up to 72 h although the rate of conversion of sugars to ethanol was reduced after 24 h. Nguyen et al (2018) obtained high yields of ethanol (33.9 g/L) from soybean residue when galactose adapted yeast was used.…”
Section: Hplc Profile Of Monosaccharidesmentioning
confidence: 60%